2019 6th International Conference on Behavioral, Economic and Socio-Cultural Computing (BESC) 2019
DOI: 10.1109/besc48373.2019.8963027
|View full text |Cite
|
Sign up to set email alerts
|

Fear of Missing Out (FoMO) as Really Lived: Five Classifications and one Ecology

Abstract: Social media provides a platform for information sharing and dissemination and has speedily become a popular method for individuals to relate to others regardless of the time and geographical distance. However, this wealth of connectivity and availability of information may lead to the experience of the Fear of Missing Out (FoMO) that typically refers to a preoccupation of the users of social media about lost opportunities when they are offline or unable to connect and communicate as wished. Despite the recogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 14 publications
0
22
0
4
Order By: Relevance
“…Previous research [ 2 , 18 , 19 ] has identified five primary contexts of use where FoMO occurs, the fears associated with them and the potential technical countermeasures. The findings are summarised in Table 1 .…”
Section: Fomo Reduction Methods (Fomo-r): Theoretical Underpinningsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous research [ 2 , 18 , 19 ] has identified five primary contexts of use where FoMO occurs, the fears associated with them and the potential technical countermeasures. The findings are summarised in Table 1 .…”
Section: Fomo Reduction Methods (Fomo-r): Theoretical Underpinningsmentioning
confidence: 99%
“…One such negative experience is the fear of missing out (FoMO). This typically refers to the preoccupation of users of social media with lost opportunities when they are offline or unable or unwilling to connect and communicate with others to the extent they wish [ 2 ]. Researchers have recently begun to explore the negative consequences of FoMO that are faced by social media users.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations